Pendekatan Konstruktivis dalam Desain Pembelajaran Pendidikan Agama Islam: The Constructivist Approach in the Design of Islamic Religious Education Learning - Ilma, Miska Unil; Ismatullah, Ade; Rosadi, Adi (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
Islamic Religious Education (PAI) learning in the modern era faces challenges in developing students' deep understanding and critical thinking skills. Traditional approaches that focus on memorization are considered less effective in achieving 21st century educational goals. Therefore, a more innovative approach is needed, one of which is the constructivist approach, which emphasizes students' active involvement in the learning process. This study aims to analyze the application of constructivist approach in PAI learning and its benefits for improving the quality of students' understanding and critical thinking skills. The method used is descriptive qualitative research with a literature study approach. Data were collected from various academic literatures related to constructivist approach and its implementation in PAI learning. The results showed that the constructivist approach can be applied in PAI learning to increase student engagement, deepen concept understanding, and develop a more critical and reflective mindset. Therefore, the implementation of this approach needs to be supported by more interactive and experiential learning strategies to make PAI learning more effective and relevant to the needs of students in the digital era.